2019
DOI: 10.1111/bjdp.12308
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychological control and academic functioning in Chinese high school students: A short‐term longitudinal study

Abstract: The present study aimed to examine the reciprocal relationship between parental psychological control and students’ academic functioning in urban China. Participants were 731 Chinese high school students in grade 10 (356 boys; Mage = 15.64 years, SD = 0.68). Two waves of 1‐year longitudinal data were collected using student reports of parental psychological control and academic‐related beliefs, strategies, and behaviours. Results showed that parental psychological control at Time 1 significantly triggered an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…We also found that goal disengagement strategies mediated the relation between maternal psychological control and academic achievement, which supported hypothesis 2a and is consistent with prior studies (Aunola & Nurmi, 2004;Pinquart, 2016). Recent findings have shown that parental psychological control is linked with adolescents' uncertainty of their academic abilities (Lu et al, 2017;Xu et al, 2020). Adolescents who experience psychological control may develop low self-efficacy overtime in domains such as academics (e.g., Filippello et al, 2015).…”
Section: Goal Disengagement and Maternal Psychological Controlsupporting
confidence: 90%
See 3 more Smart Citations
“…We also found that goal disengagement strategies mediated the relation between maternal psychological control and academic achievement, which supported hypothesis 2a and is consistent with prior studies (Aunola & Nurmi, 2004;Pinquart, 2016). Recent findings have shown that parental psychological control is linked with adolescents' uncertainty of their academic abilities (Lu et al, 2017;Xu et al, 2020). Adolescents who experience psychological control may develop low self-efficacy overtime in domains such as academics (e.g., Filippello et al, 2015).…”
Section: Goal Disengagement and Maternal Psychological Controlsupporting
confidence: 90%
“…For example, Lu et al (2017) found that adolescents who experienced strong parental attempts for psychological control had low academic self-concept. Numerous studies have also shown a negative association between parental psychological control and adolescents' academic self-efficacy and academic performance (Desjardins & Leadbeater, 2017;Xu et al, 2020). Building on this research that has revealed associations between parental psychological control and adolescents' academic outcomes, we will further investigate the mechanisms through which this effect occurs.…”
Section: Negative Parenting and Academic Difficultiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Most noticeable was a pattern of parenting that was characterized by nurturing the love of learning and self-direction early on and then having a hands-off policy once the child became more capable of taking self-initiative and navigating learning on their own. This practice becomes more illuminating when Chinese parents tend to exert much behavioral and psychological control over their children even throughout their childhood [53,54]. Of course, there could also be a child's effect on parenting in that autonomous learners rendered parental control unnecessary.…”
Section: Prior To the Programmentioning
confidence: 99%